Penerapan Metode QFD dan Kano Dalam Upaya Peningkatan Kualitas Produk Temulawak UNOWEN - Muhammad Wahyu Hidayat; Hidayat Hidayat; Efta Dhartikasari Priyana (G-Tech: Jurnal Teknologi Terapan, 2025)
Competition in the Temulawak Unowen MSME industry is getting tighter. Many other producers are also trying to enter the market with various new innovations both in terms of taste and packaging. Therefore, it is important for companies to continue to carry out product development in order to remain competitive and maintain their market share. In this study, the Kano and QFD methods were used. The purpose of the Kano Method is to find out what consumers want about cracker production, and QFD is to offer the most important suggestions for improving quality. The results showed that Kano has 12 one-dimensional attributes, 4 Indifferent attributes. On the other hand, the QFD research results show that the validity testing of all three tiers resulted in a calculated R value that is more than R table 0.55, which indicates that the attributes are valid while the reliability test shows that the alpha value of all 3 tiers is 0.663 and the respondents' answers are considered reliable.